Failure to eradicate Helicobacter pylori infection is more frequent among HIV‐positive patients. Issue 7 (25th March 2021) - Nkuize, M; Vanderpas, J; Buset, M; Delforge, M; Cadière, G‐B; De Wit, S
Abstract : Objectives: Helicobacter pylori is a worldwide infection, but little is known about the efficacy of treatment for H . pylori infection in HIV‐positive patients. The goal of this work was to evaluate outcomes after first‐line H . pylori treatment and identify risk factors for failure in HIV‐positive patients. Methods: This registry study of unmatched H . pylori ‐infected HIV‐positive patients and HIV‐negative obese pre‐bariatric surgery controls was performed in a tertiary university hospital. Cases were enrolled from 2006 to 2017, controls from 2007 to 2014, and both received standard of care. An additional 'optimal' subgroup of cases was enrolled prospectively from 2017 to 2019 which was treated only on the basis of antibiogram, drug interaction search and additional support by one referent physician. Helicobacter pylori eradication failure rates were compared according to clinical, microbiological and pathological parameters and treatment. Results: We analysed 258 HIV‐positive patients and 204 HIV‐negative control patients. Helicobacter pylori eradication failure rates were markedly greater in cases (24.1%) than in controls (8.8%). The proportions of levofloxacin and metronidazole resistance were greater in cases than in controls ( P < 0.05). Among cases treated with H . pylori triple therapy (S3T), the 'optimal' subgroup experienced a 9.5% failure rate vs . 28.6% with other strategies ( P = 0.01). Risk factors for failure were H . pylori treatment strategy, exposure to antiretroviral treatment, and alcohol status. Overall, positive HIV status was a risk factor for S3T eradication failure. Conclusions: Patients co‐infected with H. pylori and HIV frequently failed to eradicate H . pylori and this was related to treatment strategy, antiretroviral exposure and lifestyle.